(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Most of the maternity care and tertiary level hospitals have a lactation management centre. Lactation management centre is a part of the mother-baby unit and identify the problems on breastfeeding and help the mothers with breast feeding problems and promote, protect and support the breast feeding. A retrospective data was collected from registered book of 4 hospitals where Lactation management centre have. Maximum mothers had lack of knowledge on positioning and attachment. Also faced the problems such as insufficient breast milk, crack nipple, flat nipple, inverted nipple, engorge breast etc. Service was given accordingly. In some cases oketani breast massage technique was needed. The nurses of Lactation management centre were skilled enough to motivate the mothers on breastfeeding 100%. J Shaheed Suhrawardy Med Coll, 2015; 7(1):36-39